Ca2+-PKC-caspase 3-like protease pathway mediates DNA and nuclear fragmentation in ecdysteroid-induced programmed cell death - Masatoshi Iga (2018)
20-Hydroxyecdysone (20E) induces programmed cell death in the anterior silk gland of the silkworm. Here, we report the direct interaction between Ca2+ and protein kinase C (PKC)-caspase 3-like protease pathway in the 20E-induced cell death. The calcium ionophore can mimic 20E effects in inducing DNA and nuclear fragmentation, but such mimicry is only possible in the glands precultured for 18h with 20E. The simultaneous presence of translation inhibitor with 20E in the preculture showed that de novo protein synthesis was needed to mimic 20E effects by the calcium ionophore. Both a PKC inhibitor and a caspase 3 inhibitor inhibited the mimicking effects. After substitution of the calcium ionophore for 20E, caspase 3-like protease was fully activated 12h later, and DNA and nuclear fragmentation occurred faster than continuous 20E stimuli. The results show the presence of a Ca2+-PKC-caspase 3-like protease pathway in 20E signaling, and possible involvement of the pathway up to the mobilization of Ca2+ in regulating the timing of cell death in vivo. © 2010 Elsevier Ireland Ltd.